Developing Multimedia Kids Play Learning Materials for Students with Special Needs - Ageung Darajat; Muhammad Iqbal Ripo Putra; Sulaiman (Penerbit STKIP PGRI Bangkalan, 2018)
This study involved an English teacher from one of special schools in Pontianak. It is investigated the materials are the source for teachers to teach and for students to learn. Two areas of investigation were set up in this study and were aimed to explore: 1) Describing the English teaching learning process for autistic learners at CAHAYA BANGSA Pontianak; 2) Developing the materials for encouraging the students to be more involved and concentrated. This final project used the research and development (R&D) to develop the materials. The materials were validated by two experts to come to the final product. This research conducted at CAHAYA BANGSA PONTIANAK involving the students of seventh grade with special needs (in this case is autism). The data were collected from classroom and checklist observations, questionnaire and interview with teacher. Those data collection resulted that teacher and students actually confronted the same problem which was the absence of a set of suitable materials for English lesson. The integration of the materials then led to materials development for encouraging the students’ involvement and concentration. The researchers assumed there were some considerations the teacher should pay attention in using the materials, those are: 1) the teachers should give the instruction clearly to the students; 2) the teachers should be more creative in developing materials for the students; 3) the teacher should enhance her knowledge of materials development for students with special needs; 4) Every student has different characteristics, therefore the materials should be applied in the basis of students’ capacity and ability